Impact of Gender Diversity on Sustainability Performance - Mushtaq, Kashif (Pakistan Journal of Humanities and Social Sciences, 2025)
The inclusion of gender diversity has become an essential element in advancing sustainability within corporate practices and governance. However, gender diversity is a critical issue among the Pakistani organizations. This research examines the influence of gender-diverse leadership on business decision-making, sustainability initiatives, and overall organizational effectiveness by aggregating results from 67 empirical studies published between 2020 and 2024, all obtained from the Wiley Online Library. In addition, this study considered the effect of gender diversity on sustainability performance by using primary data collected by using questionnaire surveys. By using Partial Least Squares Structural Equation Modeling (PLS-SEM), it is found that the organizations that feature diverse leadership teams tend to implement robust sustainability policies, enhance stakeholder engagement, and attain better financial and environmental results. Furthermore, results revealed the positive effect of gender diversity on sustainability performance. These findings highlight the significance of promoting gender diversity in leadership roles to foster long-term value and sustainable business practices.